Overcoming the Coincidence Effect of a Single Panel by Introducing and Tuning Locally Resonant Structures - Jovanoska, Milica; Godinho, Luís; Amado-Mendes, Paulo; Mareze, Paulo Henrique; Pereira, Matheus; Ramis Claver, Erique (Institute of Noise Control Engineering, 2019)
The acoustic performance of partition walls is usually based either in their mass or in a layered structure, including materials with different properties (external layers and internal absorbing materials, for example). In recent years, the consideration of additional dynamic effects in the behaviour of such systems has been used to improve their performance. Among these new proposals, metamaterials are a promising possibility. In this paper, numerical and experimental analyses were carried out in order to investigate the sound transmission loss of a single particle board with periodically attached spring-mass resonators. The resonators were materialized by 3D printing and designed to achieve resonant frequency in the coincidence region of the panel. Both, numerical and experimental results showed that the resonance mode of the spring-mass resonators couples with the plate vibration in the way of breaking the mass law and overcoming the coincidence effect throughout the formation of a band gap in the desired frequency region. Therefore, this metamaterial design can serve as an effective solution for increasing the sound transmission loss of the panel.